Unveiling Inequalities: The Disability Wage Gap & Unequal Treatment in Neoliberal Workfare Governance in Australia, Indonesia and The United Kingdom (UK) - Turnip, Chairil Gibran Saragi (Mahadi: Indonesia Journal of Law, 2024)
Neoliberal workfare governance policies in Australia, Indonesia, and the United Kingdom have exacerbated inequalities for people with disabilities despite promises of economic growth and personal freedom. This analysis reveals persistent wage disparities, structural barriers, and marginalization faced by individuals with disabilities under market-oriented policies. In Indonesia, efforts to ensure equal opportunities in civil service recruitment have failed due to implementation failures and discriminatory practices. Neoliberal emphasis on market efficiency has prioritized cost-saving measures, perpetuating structural disparities and hindering substantive equality for individuals with disabilities.Â  In Australia, the ongoing wage gap between disabled and non-disabled workers highlights entrenched biases and systemic injustices in the labor market. People with disabilities face significant challenges in securing stable employment, resulting in lower wages and limited career opportunities. In the United Kingdom, empirical research underscores persistent barriers to employment and lower wages experienced by individuals with disabilities, exacerbated by intersecting forms of discrimination.Â  Overall, neoliberal policies have not only failed to reduce but have worsened the conditions for individuals with disabilities. Addressing these challenges requires dismantling structural barriers, promoting inclusive policies, and ensuring equitable access to employment and social support systems. Shifting from market-driven approaches to policies prioritizing substantive equality, social well-being, and human dignity for all individuals, regardless of disability status, is crucial. By challenging neoliberal paradigms and advocating for inclusive reforms, society can move towards a future that is fairer and more equitable for individuals with disabilities.